An Improved Authentication Scheme for Digital Rights Management System. (27th January 2022) - Hussain, Sajid; Zikria, Yousaf Bin; Mallah, Ghulam Ali; Chen, Chien-Ming; Alshehri, Mohammad Dahman; Ishmanov, Farruh; Chaudhry, Shehzad Ashraf
Abstract : With the increasing number and popularity of digital content, the management of digital access rights has become an utmost important field. Through digital rights management systems (DRM-S), access to digital contents can be defined and for this, an efficient and secure authentication scheme is required. The DRM authentication schemes can be used to give access or restrict access to digital content. Very recently in 2020, Yu et al. proposed a symmetric hash and xor-based DRM and termed their system to achieve both security and performance efficiency. Contrarily, in this study, we argue that their scheme has several issues including nonresistance to privileged insider and impersonation attacks. Moreover, it is also to show in this study that their scheme has an incorrect authentication phase and due to this incorrectness, the scheme of Yu et al. lacks user scalability. An improved scheme is then proposed to counter the insecurities and incorrectness of the scheme of Yu et al. We prove the security of the proposed scheme using BAN logic. For a clear picture of the security properties, we also provide a textual discussion on the robustness of the proposed scheme. Moreover, due to the usage of symmetric key-based hash functions, the proposed scheme has a comparable performance efficiency.